Project Risk Register Analysis Based on the Theoretical Analysis of Project Management Notion of Risk - Uzulāns Juris (Economics and Business)
The aim of the current research is to examine publicly available project risk registers to find correlations between the project management theory, especially project risk management, and practical results of real project risk management – the risk registers publicly available on the Internet.